(untitled) (Journal Of Educational and Psychological Researches, 2024)
The current research aims to identify the reality of institutional efficiency at Omani universities from the point of view of faculty members. The research used a comparative-descriptive research approach. A questionnaire consisting of 24 items was developed. Its validity and reliability were verified. The research sample consisted of 204 faculty members who were selected using the convenience sampling method from Sultan Qaboos University and the University of Nizwa. The results showed that the reality of institutional efficiency at Omani Universities from the point of view of its faculty members was large. Statistically significant differences were found in the estimates of the study sample of the reality of institutional efficiency due to the university variable in favor of Sultan Qaboos University. There are statistically significant differences due to the variable years of experience in university service favoring faculty members who have experience of 7 years or less. The research recommended emphasizing the importance of improving the institutional performance of Omani universities in general and private universities in particular